The Inner Enemies of Democracy. (March 2016) - Mercer, Ben
Abstract : The Inner Enemies of Democracy. By Tzvetan Todorov, trans. Andrew Brown (Malden, MA: Polity Press, 2014), pp.vi + 201. £20.00 (cloth).